Od małego „Dyzia” do dorosłego „rycerza z La Manchy”. Analiza problemu marzycielstwa u dzieci i młodzieży z perspektywy kulturowo-historycznej teorii rozwoju - Gąsiorek , Przemysław (Studia Edukacyjne, 2021)
This study describes the issue of maladaptive daydreaming. This phenomenon is becoming a contemporary educational problem because it limits the development potential of children and adolescents as well as their interpersonal relations. The field of possible understanding of maladaptive daydreaming in relation to terms related in meaning was outlined, as well as the current attempts at its scientific conceptualization. In my analysis, I go beyond the dualistic understanding of the children’s real and imaginary world, referring to the cultural-historical theory of the development of creative imagination as a higher mental function as an internalized system of social relations. From this perspective, the phenomenon of daydreaming in children and adolescents, in relation to reality, is not treated in a dichotomous way, but as a social development situation.